Heterologous expression of the 65-kilodalton antigen of Mycobacterium leprae and murine T-cell responses to the gene product. - Lamb, F I (1988)
The gene encoding the immunodominant 65-kilodalton antigen of Mycobacterium leprae was subcloned from a lambda gt11 clone into the high-copy-number plasmid pUC8. Escherichia coli containing these recombinants produced large amounts of the antigen, which was purified by polyacrylamide gel electrophoresis in the presence of urea. The ability of E. coli to recognize the mycobacterial promoter was confirmed by constructing additional clones in which the gene is flanked by transcriptional terminators from phage fd. A similar approach was used to demonstrate the expression of this gene in Streptomyces lividans. Mice immunized with killed M. leprae showed cell-mediated immune reactivity to the purified 65-kilodalton protein which stimulated both in vitro lymphoproliferative and in vivo delayed-type hypersensitivity responses.